Promosi Perpustakaan Melalui Bulletin di Perpustakaan “HAMKA” SD Muhammadiyah Condongcatur: Best Practice - Nurrohmah Hidayah (Institut Agama Islam Negeri Salatiga, 2018)
This paper aims to explain the development of promotional products in Library elementaryMuhammadiyah Condongcatur, through the creation of library bulletins.In this study, the authors aim to explain the six stages in the implementation of thisprogram: 1) analyze user needs, 2) build partnerships, 3) develop activities and resources,4) implementation of promotion, 4) evaluation. The results of this study isa bulletin product that can be used as a library promotion tool and as an activity toincrease interest in reading and writing for all school civitas. The program in this studyneeds to be addressed as there are many other elementary school libraries to developpromotion at the primary school level.